Influence of Clothing Visual Marketing Path on Consumers’ Purchasing Intention - Lyu , Xingyu; Niyomsilp, Eksiri (Journal of Roi Kaensarn Academi, 2021)
How to meet the growing demands of new consumers the influential relationship between the visual marketing journey of apparel brands and consumers was discussed under the circumstances of multimedia convergence. and visual marketing and related theories on brand image perception and perceived value. was taken into account the relational model of the influence of the 6 Paths of Visual Marketing on Purchase Intent is was established. The method of interview by interviewing the sample, questionnaire inquiry, and structural equation modeling were used. Finally, the examination and empirically analyzation of the research hypothesis were taken. The results showed that the most influential factors for customer loyalty and satisfaction are co-branding and fashion show activities in the visual marketing path of clothing, followed by offline stores and short videos. The consumers’ purchasing intentions are influenced by the scene, window, dressing room environment, brand identity image, corporate image, network image of the offline physical stores and social platform. Moreover, the effect of consumer satisfaction on purchase intention is higher than that of consumer loyalty.